2008
DOI: 10.1097/sap.0b013e3181723bbe
|View full text |Cite
|
Sign up to set email alerts
|

Regional Anatomic and Age Effects on Cell Function of Human Adipose-Derived Stem Cells

Abstract: Adipose tissue has been shown to contain adult mesenchymal stem cells that have therapeutic applications in regenerative medicine. There is evidence that the ability of adipose precursor cells to grow and differentiate varies among fat depots and changes with age. Defining these variations in cell function and molecular mechanisms of adipogenesis will facilitate the development of cellbased therapies. We compared cells harvested from 5 different subcutaneous (SC) adipose depots in 12 female patients classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
234
2
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(251 citation statements)
references
References 17 publications
7
234
2
8
Order By: Relevance
“…Adipose tissue from the abdomen, waist, thigh and inner knee revealed no significant differences with regard to the viability profile of cells. Superficial abdominal depot has also been shown to less susceptible to apoptosis compared to ASCs from other regions (20). However, we did not observe significant differences in viability profiles among donor areas.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Adipose tissue from the abdomen, waist, thigh and inner knee revealed no significant differences with regard to the viability profile of cells. Superficial abdominal depot has also been shown to less susceptible to apoptosis compared to ASCs from other regions (20). However, we did not observe significant differences in viability profiles among donor areas.…”
Section: Discussioncontrasting
confidence: 50%
“…It has been shown that ASCs from younger patients hold a greater proliferative capacity and are more efficient in differentiating into mature adipocytes than those from older patients (20), rendering younger patients more suitable for tissue engineering applications. In the present study, the mean age was 41.5 years, significantly less than the age group of 55-60 that displays the highest apoptotic rates (20).…”
Section: Discussionmentioning
confidence: 99%
“…While an analysis of breast tissues specimens from >180 women donors aged 16-73 did not observe an age dependent difference in stromal cell numbers or adipogenesis, increased body mass index correlated significantly with reduce cell numbers and differentiation [9]. Clinical studies examining subcutaneous adipose tissue from 12 to 52 donors have reported reduced ASC adipogenesis, angiogenesis, osteogenesis, and/or proliferative capacity as a function of advancing donor age [10][11][12]. Similarly, a detailed comparison of five different subcutaneous depots determined that ASC isolated from the arm and thigh best maintained adipogenic potential as a function of advancing age [12].…”
Section: Donor Considerationsmentioning
confidence: 99%
“…Clinical studies examining subcutaneous adipose tissue from 12 to 52 donors have reported reduced ASC adipogenesis, angiogenesis, osteogenesis, and/or proliferative capacity as a function of advancing donor age [10][11][12]. Similarly, a detailed comparison of five different subcutaneous depots determined that ASC isolated from the arm and thigh best maintained adipogenic potential as a function of advancing age [12]. Further studies in larger cohorts will be necessary before patient demographics can be used to predict the functionality and recovery of SVF cells and ASCs from donors as well as the relative utility of specific depot sites.…”
Section: Donor Considerationsmentioning
confidence: 99%
“…In contrast to HSCs, MSCs can be grown more easily and can differentiate into mesoderm-derived tissues, while HSCs can re-constitute the haemopoeitic system. MSCs can be selectively grown into bone cells (osteocytes) [8], fat cells (adipocytes) [9] and cartilage cells (chondrocytes) [10] which made them an attractive choice for bone and cartilage tissue engineering as autologous transplants [11,12]. Moreover, they are now considered a routine medical procedure in treating leukemia patients in addition to HSCs [13].…”
Section: Introductionmentioning
confidence: 99%